Problema Sosial, Pandangan Hidup dan Konsep Kebudayaan - Zulkifli Lubis (Antropologi Indonesia, 2011)
This paper reviews various social issues in the trajectory of the author’s life to connect the concept of the view of life and theoretic issues on culture. Through methodological reflections, the author presents various issues which are being constantly discussed in the public mass media about religion, cultural icons as well as daily practices which become entry points to see cultural diversity as well as changes that can be found in the trajectory of life. The author argues that the individual is active in formulating the culture even though it cannot be denied that it can only be articulated through culture as a network of meanings as agreed by the aggregate of individuals or groups. Keywords: social problems, cultural make up, culture, view of life